Митні делікти у сфері міжнародних поштових та експрес-відправлень: сутність, формування і класифікація - Фрадинський, Олександр Анатолійович (My University, 2020)
Стаття присвячена питанням дослідження митних правопорушень у сфері міжнародного поштового обміну та експрес-відправлень. Зроблено висновок, що митні делікти у цій сфері є відносно новим різновидом митних правопорушень, який сформувався завдяки виникненню й розвитку міжнародного поштового обміну та полягає у здійсненні контрабандних дій і порушень митних правил із використанням засобів та можливостей поштового обміну та експрес-перевезень визначення митного делікту. Обґрунтовано доцільність виокремлення передумов їх вчинення на універсальні (притаманні для усієї митної системи) та специфічні (які несуть у собі ознаки, що випливають із особливостей функціонування міжнародного поштового обміну).

Customs torts account for a significant share in the shadow economic activity of society, directly affecting the state of economic and nationalsecurity of the state. The purpose of the paper is research of theoretical and practical aspects of committing customs offenses in the field of international postal exchange (IPE). The theoretical and methodological basis is the domestic legal framework, scientific works of domestic and foreign scientists and practitioners, statistical information of the State Customs Service of Ukraine. The results of the study were obtained through the use of a dialectical method of cognition of phenomen that have a legal and economic nature and relate to approaches to customs control and registration of international postal exchange. As a result of applying the method of analysis, approaches to the classification of customs torts in the field of international postal exchange were outlined. It is noted that customs delinquency in the field of IPE is a relatively new type of customs offenses, which was formed due to the emergence and development of international postal exchange and consists in smuggling and violations of customs rules using means and opportunities of postal exchange and express transportation to determine customs delinquency. The expediency ofseparating the preconditions for their commission into universal (inherent to the entire customs system) and specific (which bear the features arising from the peculiarities of the functioning of international postal exchange) is substantiated. Prerequisites for the occurrence of customs torts in the international postal exchange should be divided into: universal (inherent in the entire customs system) and specific (which have features arising from the peculiarities of the functioning of international postal exchange). It is advisable to classify them according to the most pronounced features: depending on the type of offense; depending on the type of customs risk; depending on the method of committing a customs tort; depending on the type of international mail; by type of entities involved in international postal exchange; by types of contraband or violations of customs regulations; depending on the type of liability; depending on the residence of the subjects of international postal exchange; depending on the degree of social organization of the subjects of international postal exchange; by frequency of commission; depending on the amount of damage. The scientific and methodological apparatus for the study of customs torts in the field of international postal exchange has been expanded by providing an author’s definition of this phenomenon, outlining the preconditions for its formation and classification. Proposals have been developed to improve customs formalities in the field of international postal exchange in the context of three areas ‒ the exchange of preliminary customs information, the establishment of stricter limits on the movement of international postal and express shipments, post-customs audit.
Keywords: митниця; делікт; контрабанда; порушення митних правил; міжнародний поштовий обмін; експрес-відправлення; customs; tort; smuggling; violation of customs regulations; international postal exchange; express shipment